Providing a positive learning experience for international students studying at UK universities: A literature review. (April 2014) - Lillyman, Sue; Bennett, Clare
Much of the current literature relating to international students at university level tends to highlight their experiences from a deficit perspective and in some cases even problematises the experience for the student and university. Other studies tend to focus on recruitment and motivation rather than the lived experiences of the student, thereby providing little assistance to guide the student, academic and host university in their preparation for, and working with, the international student. International students choose to study in the United Kingdom for a variety of positive reasons. However, these factors have the potential to become stressors as the student makes the transition to studying in a foreign country. Rather than viewing these stressors from a negative perspective, this literature review identifies how, with planning, support and understanding, universities can provide and develop a positive experience for all concerned.